2021
DOI: 10.26842/binhm.7.2021.16.3.0267
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Predator and Parasitoid Insects in Duhok Province, Kurdistan Region, Iraq

Abstract: A total of 47 species belonging to 46 genera, 34 subfamilies, 23 families and 7 orders of predator and parasitoid insects were collected and identified. The survey was conducted throughout the program held by the General Directorate of Agriculture-Duhok, in cooperating with the College of Agricultural Engineering Sciences in Duhok Province, Kurdistan Region, Iraq from May 2013 to April 2014. The species hosts, collecting date, locality and distributions are given. The current checklist also included some speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…It was revealed that the North of Iraq had the most observed parasitoids and aphids. Generally, there were fewer parasitoids than aphids belonging to the families Braconidae and Aphelinidae, which have many parasitoid species (Bandyan et al, 2021;Hassan, 2021). Our research suggests that aphid parasitoids may be found on the broad bean plants because of the aphid infestation that locates damaged plants and identifies aphid insects on the infested plant by detecting the host plants.…”
Section: The Parasitoids Species On a Fabaementioning
confidence: 76%
“…It was revealed that the North of Iraq had the most observed parasitoids and aphids. Generally, there were fewer parasitoids than aphids belonging to the families Braconidae and Aphelinidae, which have many parasitoid species (Bandyan et al, 2021;Hassan, 2021). Our research suggests that aphid parasitoids may be found on the broad bean plants because of the aphid infestation that locates damaged plants and identifies aphid insects on the infested plant by detecting the host plants.…”
Section: The Parasitoids Species On a Fabaementioning
confidence: 76%